2006
DOI: 10.1016/j.pain.2006.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Physical and psychological factors maintain long-term predictive capacity post-whiplash injury

Abstract: Higher initial levels of pain and disability, older age, cold hyperalgesia, impaired sympathetic vasoconstriction and moderate post-traumatic stress symptoms have been shown to be associated with poor outcome 6 months following whiplash injury. This study prospectively investigated the predictive capacity of these variables at a long-term follow-up. Sixty-five of an initial cohort of 76 acutely injured whiplash participants were followed to 2-3 years post-accident. Motor function (ROM; kinaesthetic sense; acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
262
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(279 citation statements)
references
References 17 publications
11
262
2
4
Order By: Relevance
“…It is noteworthy that PPT_remote, in tandem with CPT, held in the regression model for TUF (P = 0.1). This may align with previous work demonstrating that chronic WAD can result in findings of not just local, but rather widespread abnormal pain processing [2,10,52]. However, the direction of the association between PPT_local, TF (P = 0.09) and TUF (P = 0.1) was inverse (e.g., those with higher fat content had higher thresholds) and this is more difficult to explain.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is noteworthy that PPT_remote, in tandem with CPT, held in the regression model for TUF (P = 0.1). This may align with previous work demonstrating that chronic WAD can result in findings of not just local, but rather widespread abnormal pain processing [2,10,52]. However, the direction of the association between PPT_local, TF (P = 0.09) and TUF (P = 0.1) was inverse (e.g., those with higher fat content had higher thresholds) and this is more difficult to explain.…”
Section: Discussionsupporting
confidence: 86%
“…However, as these findings of fatty infiltrate were observed in the chronic state, the significance of these muscle changes with respect to outcomes such as pain and disability and recovery rates remains unclear. The participants of this study all showed concomitant sensory (hyperalgesia) and psychological disturbances that characterize and predict those with a complex, non-resolving injury [52]. These disturbances have not shown to feature in subjects with persistent non-traumatic neck disorders [48].…”
Section: Discussionmentioning
confidence: 79%
“…1 Half of all those exposed to a MVC will never fully recover but have milder symptoms, 2 and 25% (~ 1 million) are expected to present with a complex clinical picture including severe-pain-related disability, 3 muscle degeneration, 4,5 sensory and motor disturbances, 6 muscle weakness, 7 and psychological distress. 6 A number of psychosocial factors (e.g., coping, expectations, anxiety and depression) have been identified as being associated with poor functional recovery. 2 Despite the presence of and recognition for these factors, current best multimodal treatments have not substantially influenced the rate of functional recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms such as altered central pain processing and central sensitization [8][9][10][11] and the role of cognitions and behaviors [12][13][14][15] have been suggested, and evidence that supports these theories is rising. The dearth of trials evaluating conservative treatments for patients with chronic WAD is striking.…”
Section: Introductionmentioning
confidence: 99%